Replacement of the esophagus the stomach with forming invaginated antireflux mechanism at the child with VATER association - Marat Ospanov; Yuryi Olkhovik; Dastan Rustemov; Rustem Utebaliev (National Scientific Medical Center, 2016)
The observation is described the successful treatment of the child with VATER association. We made the correction of esophageal atresia with lower trachea-oesophageal fistula, anal atresia withrectourethral fistula. Performed surgical operations: retrosternal esophagoplasty the stomach, gastrooesophageal anastomosis in the neck with an antireflux mechanism, anosphincteroplasty.